2020
DOI: 10.21203/rs.3.rs-125856/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Assessment of Genetic Diversity in Traditional Landraces and Improved Cultivars of Rice

Abstract: Background: Rice is the staple food for more than half of the world's population. Rice cultivation needs expansion to meet the increasing food demands across the globe. Genetic diversity is desired for crop breeding because it serves as the backbone for improving cultivars. The process of domestication and modern plant breeding technologies applied to rice has contributed to the erosion of genetic diversity. Current breeding programs have extensively shaped the genetic diversity of elite rice cultivars to no s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 77 publications
0
2
0
Order By: Relevance
“…So, the utmost importance should be given to these characters during the selection for yield improvement in rice. Zahra et al (2020) [36] found that modern cultivars have a narrow genetic base compared to landraces. Therefore, exploring the genome of landraces at a large scale to identify the genes responsible for stability and adaptation to abiotic stresses can help design varieties that can survive vulnerable climates.…”
Section: Molecular Breeding Approaches For Crop Improvement Using Traditional Rice Landracesmentioning
confidence: 99%
“…So, the utmost importance should be given to these characters during the selection for yield improvement in rice. Zahra et al (2020) [36] found that modern cultivars have a narrow genetic base compared to landraces. Therefore, exploring the genome of landraces at a large scale to identify the genes responsible for stability and adaptation to abiotic stresses can help design varieties that can survive vulnerable climates.…”
Section: Molecular Breeding Approaches For Crop Improvement Using Traditional Rice Landracesmentioning
confidence: 99%
“…Landraces that endowed with tremendous genetic variability support the adaptation of landraces to wide agro-ecological niches. Landraces are precious genetic resources because they contain rich variability of agronomical important and complex quantitative traits, which have not been widely utilized or incorporated into modern varieties (Rao et al 2018;Zahra et al 2020). Assessing genetic variability for growth, yield, and grain quality characters among the local landraces is an important step before starting a crop breeding program to incorporate traits of interest.…”
Section: Introductionmentioning
confidence: 99%